IMPLEMENTASI NILAI PENDIDIKAN DALAM KEGIATAN RATIB AL-ATTAS DI MI AL-AWWAL PALEMBANG - Cindai; Middya Boty; Ines Tasya Jadidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of educational values in the Ratib Al-Attas activities at MI Al-Awwal Palembang. The background of this research is based on the importance of strengthening students' character through religious habituation activities in Islamic educational institutions. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results showed that the implementation of Ratib Al-Attas activities contains various educational values, including religious values, discipline, social values, and moral values. These values are instilled through routine activities, teacher guidance, and student participation. Supporting factors include institutional support, teacher involvement, and student enthusiasm, while inhibiting factors include limited time and variations in student understanding. Overall, this activity contributes positively to shaping students' character and spiritual awareness.